Capsule Endoscopy in Children - Cohen, Stanley A.; Oliva, Salvatore (Frontiers in Pediatrics, 2021)
Since its clearance for use throughout the world, capsule endoscopy (CE) has become part of our pediatric diagnostic armamentarium, helping us to understand and document both normal and abnormal findings in the small intestine, especially since it usually can be employed without sedation or radiation. The indications in children and adults are similar, though their relative frequencies are different, with evaluation of potential and known inflammatory bowel disease the most common in the pediatric population, with CE also yielding increased diagnostic certainty compared to radiographic studies and surrogate biomarkers. Newer capsules now create opportunities to expand that understanding and our practices so that we can learn when and how to employ CE and panenteric CE to better monitor and guide therapy. This will take further studies to determine the best uses for CE and how to select the appropriate candidates, especially with ongoing concern about capsule ingestion versus placement, the potential for capsule retention (particularly in known Crohn’s disease), still elusive, optimal methods for bowel cleansing and the most meaningful scoring for research and clinical use.